The Influence of Ability and Work Environment on Employee Performance - Florinsky, Sisilia Natasya; Ambarwati, Titiek; Robbie, Iqbal (Universitas Muhammadiyah Malang, 2023)
This study aims to determine the effect of ability and work environment on employee performance at Putra Masa Depan cigarette company. This research was conducted on production employees with a total of 72 respondents. The sampling technique of this study used proportional sampling. The type of research used is explanatory research. The data collection technique used was distributing questionnaires. Data analysis was performed using the SPSS statistical application using multiple linear regression. From the results of data analysis, it was found that ability has a positive and significant effect on employee performance, the work environment has a positive and significant effect on employee performance, and ability is the variable that most influences employee performance.